An adaptive threshold based image processing technique for improved glaucoma detection and classification. Issue 2 (November 2015) - Issac, Ashish; Partha Sarathi, M.; Dutta, Malay Kishore
Highlights The optic nerve head region is analyzed for glaucoma diagnosis. Adaptive threshold based segmentation of optic disc and cup is implemented. CDR, NRR and blood vessel area as per ISNT rule are selected as features. An accuracy of 94.11% with sensitivity of 100% is achieved using SVM classifier.